Environmental law - Baird, Rachel J. (Pyrmont, N.S.W. : Thomson Reuters (Professional) Australia, 2013)
Lawbook Co. Nutshells are the essential revision tool. They provide a concise outline of the principles for each of the major subject areas within undergraduate law. Written in clear, straight forward language.
Includes bibliographical references and index.
Keywords: Environmental law -- Australia